Olmesartan Inhibits Cardiac Hypertrophy in Mice Overexpressing Renin Independently of Blood Pressure: Its Beneficial Effects on ACE2/Ang(1–7)/Mas Axis and NADPH Oxidase Expression. Issue 6 (June 2016) - Tanno, Tomohiro; Tomita, Hirofumi; Narita, Ikuyo; Kinjo, Takahiko; Nishizaki, Kimitaka; Ichikawa, Hiroaki; Kimura, Yoshihiro; Tanaka, Makoto; Osanai, Tomohiro; Okumura, Ken
Abstract : Abstract: Enhanced renin–angiotensin activity causes hypertension and cardiac hypertrophy. The angiotensin (Ang)-converting enzyme (ACE)2/Ang(1–7)/Mas axis pathway functions against Ang II type 1 receptor (AT1R) signaling. We investigated whether olmesartan (Olm), an AT1R blocker, inhibits cardiac hypertrophy independently of blood pressure, and evaluated the potential mechanisms. The 3- to 4-month-old male mice overexpressing renin in the liver (Ren-Tg) were given Olm (5 mg/kg/d) and hydralazine (Hyd) (3.5 mg/kg/d) orally for 2 months. Systolic blood pressure was higher in the Ren-Tg mice than in wild-type littermates. Olm and Hyd treatments lowered systolic blood pressure to the same degree. However, cardiac hypertrophy, evaluated by echocardiography, heart weight, cross-sectional area of cardiomyocytes, and gene expression, was inhibited by only Olm treatment, but not by Hyd. Olm treatment reversed decreased gene expressions of ACE2 and Mas receptor of Ren-Tg mice and inhibited enhanced NADPH oxidase (Nox)4 expression and reactive oxygen species, whereas Hyd treatment had no influence on them. These findings indicate that Olm treatment inhibits cardiac hypertrophy independently of blood pressure, not only through its original AT1R blockade but partly through enhancement of ACE2/Ang(1–7)/Mas axis and suppression of Nox4 expression. Abstract : Supplemental Digital Content is Available in the Text.